In Silico Molecular Docking Studies of Lichen Metabolites against Cyclooxygenase-2 Enzyme - Khan, Mohammad Firoz; Nabila, Sabreena Aleem; Rashid, Ridwan Bin; Rahman, Mohammad Sharifur; Chowdhury, Abu Asad; Rashid, Mohammad Abdur (Bangladesh Pharmaceutical Journal, 2015)
Cyclooxygenase-2 (COX-2) is an inducible enzyme that causes inflammation. COX-2 inhibitors are clinically effective anti-inflammatory agents with less gastrointestinal and renal toxicities. However, they lack anti-thrombotic activity and hence lead to increased incidences of adverse cardiovascular thrombotic events, including myocardial infarction. Therefore, there is still need to develop COX-2 inhibitors with better therapeutic effects and tolerability. The aim of the present study is to explore the anti-inflammatory activity of five lichen metabolites by conducting virtual screenings. In this regard, molecular docking simulations were carried out for the lichen metabolites namely atranorin, diffractic acid, lecanoric acid, salazinic acid and usnic acid with human COX-2 enzyme and the docked results were compared with the standard reference ligands (Celecoxib and Rofecoxib). Among all the docked ligands, the lecanoric acid demonstrated best binding affinity -9.83 kcal/mol followed by atranorin (-8.7 kcal/mol) and diffractic acid (-8.6 kcal/mol) which are comparable to the reference ligands celecoxib (-12.3 kcal/mol) and rofecoxib (-11.2 kcal/mol). The salazinic acid and usnic acid has shown binding affinity of -7.9 kcal/mol and -4.7 kcal/mol, respectively. Moreover, all the ligands except atranorin and diffractic acid satisfied Lipinskis rule of 5. From the docking results it was revealed that the lichen metabolites might have inhibitory activity against COX-2 enzyme, and are expected to be useful in conducting in vivo anti-inflammatory screenings on animal model which may lead to the development of more effective and potent new chemical entities with anti-inflammatory properties. Bangladesh Pharmaceutical Journal 18(2): 90-96, 2015